Vitamin D can be used as a supplement against cancer stem cells - Koçak, Nadir; Nergiz, Süleyman; Yıldırım, ć°brahim Halil; Duran, Yağmur (Cellular and Molecular Biology, 2018)
Cancer is standing like a bottomless pit or a black hole in front of mankind. Scientists are trying all possible ways to find a solution against to cancer. As known, cancer is a phenomenon fed from internal dynamics. One of internal dynamic is cancer stem cells that are involved in the formation and development of cancer. Because of these dynamics, scientists began to search solution inside of the body. Another internal dynamic is vitamin D and it is not only important in calcium homeostasis but also it is important for cell proliferation, differentiation, and apoptosis. In this study, we investigated the effect of vitamin D on cancer stem cells that sorted from MCF-7 cell line and on HEK293 cell line as control. Our results showed that calcitriol treatment reduced the number of CSC (Cancer Stem Cell) in the MCF-7 cell while increased in HEK293 cell population. Gene expression analyses showed that effect of calcitriol on apoptosis plays an important role in this reduction. Deficiency or unavailability of vitamin D may take a role in the pathogenesis of breast cancer.